New Perception to Proto History Burial Site in Andarawewa An Archaeological and Geochemical Prospection - Young, Sansfica M; Mendis, D. Thusitha; Ishiga, H. (Department of Archaeology, University of Kelaniya, 2020)
The megalithic burial site at Galgamuwa Andarawewa is situated at Anamaduwa Secretariat Division in the North Western Province, Sri Lanka. It is evident that 2500 years ago the proto history people had settled in this region. For burying of bodies, they have constructed different types of burials in several places in this region. Thus, to examine the geochemical prospection soil samples from the context (n=12), the glass bead samples from the furnace (n=3) and slag (n=2) were analyzed using X-Ray Fluorescence (XRF) for 22 major and trace elements. For the archaeological prospection, new findings of proto-history burials were found in the excavation carried out at Andarawewa and also many archaeological evidences were found through the field survey and excavations such as beads, inscriptions, pots and shard and chisels. The elemental values of the slag show that, Pb (470-483 mg/Kg) and Cu (855-1083 mg/Kg) are very much higher than Upper Continental Crustal Values. The white part contains higher Pb and Cu than the dark part of the slag. The concentrations of halides F, Br and I are almost similar in the white (glass) part and dark (slag) part. The Pb, Cu and as in the glass beads of the Andrawewa furnace shows that they range between 390-2920, 275-1411 and 12-127 mg/Kg respectively. However, the Fe and Ti concentrations are much lower than in the contexts though P2O5 is higher in the bead samples. The soil samples from the contexts of the area does not show high values for almost all the measured elements. Thus, indicating that the soils are local while the beads may have been prepared with sands brought from other areas. The carbon dating has dated that this burial belongs to the period from 500- 507 B.C.
Keywords: Burial, Soil, Geochemical, Slag, Glass bead